Pengaruh Ulasan Produk dan Rating Pengguna terhadap Keputusan Pembelian di Platform E-Commerce - Sahrudin, Karman; Faddil, Hafsari Prabhamanik; Faddila, Syifa Pramudita (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of digital technology has driven the rapid growth of e-commerce as a primary medium for buying and selling transactions. In this context, product reviews and user ratings have become important factors influencing consumer purchasing decisions. This study aims to analyze the influence of product reviews and user ratings on purchase decisions on e-commerce platforms. The research method used is quantitative with a survey approach, where data were collected through questionnaires from 100 respondents who have shopped online. The analysis technique used is multiple linear regression to test the effect of independent variables on the dependent variable. The results show that both product reviews and user ratings have a significant effect on purchasing decisions, both partially and simultaneously. These findings highlight the importance of interactive features on e-commerce platforms as determinants of consumer behavior. The implications of this research can serve as a reference for businesses in managing product reputation and increasing consumer trust through positive review content and a transparent rating system.